A Comparative Study of Energy Contents in Mosquito Vectors of Malaria and Dengue Prevailing in Jodhpur City (Thar Desert) of Rajasthan State, India - Suman Sundar Mohanty; Sunita Meena; Phool Chand Kanojia (Tehran University of Medical Sciences, 2018)
Background: Transmission of malaria and dengue in the desert part of India is mainly caused by Anopheles stephensi and Aedes aegypti respectively. The maintenance and transmission of the pathogens that cause malaria and dengue are dependent on the physiology of the mosquito vectors. We aimed to measure the energy contents in the mosquitoes transmitting malaria and dengue in the desert part of the country. Methods: Immature stages of mosquitoes were collected from six different larval habitats situated in Jodhpur City of Rajasthan state, India. The immature stages of both the mosquitoes were collected once in fortnightly from each location. Quantitative estimations of the lipid, glucose, and glycogen of the laboratory-reared and field collected An. stephensi and Ae. aegypti were made by spectrophotometric method. The energy contents of the larvae, pupae, females, and males were estimated in triplicates on six different occasions. Results: The lipid content of laboratory-reared larvae, pupae and female mosquitoes of An. stephensi and Ae. aegypti was found to be lower than their conspecific field-collected specimens. Whereas, the glycogen content in the laboratory-reared larvae, pupae and female mosquitoes of An. stephensi and Ae. aegypti was higher than that of their conspecific field-collected specimens. The glucose content in all the stages of the laboratory-reared An. stephensi was lower than their conspecific field-collected specimens except in few cases. Conclusion: The higher amount of lipid in field-collected mosquitoes may be because of the availability of food in the natural habitat and adaptation of mosquitoes. Mosquitoes living in desert climate are physiologically better equipped to survive in the desert environment.